3D Periodic Cellular Materials with Tailored Symmetry and Implicit Grading. (November 2021) - Efremov, Semyon; Martínez, Jonàs; Lefebvre, Sylvain
Abstract: Periodic cellular materials allow triggering complex elastic behaviors within the volume of a part. In this work, we study a novel type of 3D periodic cellular materials that emerge from a growth process in a lattice. The growth is parameterized by a 3D star-shaped set at each lattice point, defining the geometry that will appear around it. Individual tiles may be computed and used in a periodic lattice, or a global structure may be produced under spatial gradations, changing the parametric star-shaped set at each lattice location. Beyond free spatial gradation, an important advantage of our approach is that elastic symmetries can easily be enforced. We show how shared symmetries between the lattice and the star-shaped set directly translate into symmetries of the periodic structures' elastic response. Thus, our approach enables restricting the symmetry of the elastic responses – monoclinic, orthorhombic, trigonal, and so on – while freely exploring a wide space of possible geometries and topologies. We make a comprehensive study of the space of symmetries and broad combinations that our method spans and demonstrate through numerical and experimental results the elastic responses triggered by our structures. Graphical abstract: Highlights: 3D periodic cellular materials are an essential ingredient in additive manufacturing. We study a novel type of 3D periodic materials that emerge from a growth process. Our approach enables restricting the symmetry of the elastic responses. We provide numerical and experimental results of the structures' elastic properties.